2022
DOI: 10.1097/bpo.0000000000002160
|View full text |Cite
|
Sign up to set email alerts
|

Can Over-containment Prevent Recurrence in Children With Cerebral Palsy and Hip Dysplasia Undergoing Hip Reconstruction?

Abstract: Introduction: Hip reconstruction is often necessary in children with cerebral palsy (CP) but is associated with high failure rates. Over-containment deeply seats the hip within the acetabulum at the time surgical reconstruction. The goal of this study is to evaluate the effect of over-containment on radiographic outcomes and failure rates in children with CP undergoing hip reconstruction. Methods: This study is a retrospective chart review of children with CP that underwent hip reconstruction between 2010 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…By corollary, protection of the femoral head by overcontainment (MP ≤ 0%) may prevent progressive femoral head deformity by shielding it from external pressure, allowing for better force distribution across the epiphysis. Zakrzewski 19 reported lower failure rates and better radiographic parameters for hips that underwent overcontainment versus those with an MP > 0%, although FHS was not assessed in their study.…”
Section: Discussionmentioning
confidence: 91%
“…By corollary, protection of the femoral head by overcontainment (MP ≤ 0%) may prevent progressive femoral head deformity by shielding it from external pressure, allowing for better force distribution across the epiphysis. Zakrzewski 19 reported lower failure rates and better radiographic parameters for hips that underwent overcontainment versus those with an MP > 0%, although FHS was not assessed in their study.…”
Section: Discussionmentioning
confidence: 91%
“…A review of hip reconstructions in patients with cerebral palsy found a failure rate of 13% and found that a patient age of <6 years or MP >70% was associated with a higher risk of failure, whereas performing a pelvic osteotomy for an acetabular index of >25° was protective against failure 48 . A separate study found that over-containment can decrease the risk of failure, especially in nonambulatory children with substantial hip subluxation at an early age 49 .…”
Section: Cerebral Palsymentioning
confidence: 98%
“…A group from Cincinnati (Ohio, USA) sought to evaluate their clinical and radiological experience of over-containment in a single institutional retrospective study. 3 The recorded CP patients undergoing hip reconstruction over a nine-year period, with at least two years of follow-up, were examined. Migration percentage (MP), acetabular index (AI), and neck-shaft angle (NSA) were recorded pre- and postoperatively, and through follow-up, with a MP at latest follow-up ≥ 30%, or the need for revision surgery, defined as a failure of treatment.…”
Section: Can Over-containment Succeed As a Strategy In Cerebral Palsy...mentioning
confidence: 99%